A new genus and species of Mantoididae (Mantodea) from the Brazilian and Venezuelan Amazon, with remarks on Mantoida Newman, 1838 - Agudelo R., Antonio A. (Zootaxa, 2014)
Paramantoida amazonica n. gen. & n. sp. is described from North Amazon. The new genus is characterized by having anterior femora without postero-ventral spines or with 1–2 spinules (small spines) at most. Additional remarks on the genus Mantoida, following the examination of several primary types, are also presented. As a result, the identity of Manti-llica beieri Kaltenbach, 1957 as a member of Mantoida is herein confirmed, whereas other synonyms previously established for other species of Mantillica in relation to Mantoida are discarded.